The role of post-exercise nutrient administration on muscle protein synthesis and glycogen synthesis - Poole, C.; Wilborn, C.; Taylor, L.; Kerksick, C. (Journal of Sports Science & Medicine, 2010)
Nutrient administration following an exercise bout vastly affects anabolic processes within the human body, irrespective of exercise mode. Of particular importance are protein and carbohydrates whereby these two macronutrients portray distinct functions as anabolic agents. It has been confirmed that protein and/or amino acid ingestion following resistance training is required to reach a positive protein/nitrogen balance, and carbohydrate intake during recovery is the most important consideration to replenish glycogen stores from an exhaustive exercise bout. Several factors play significant roles in determining the effectiveness of protein and carbohydrate supplementation on post-exercise protein and glycogen synthesis. Improper application of these factors can limit the body's ability to reach an anabolic status. The provided evidence clearly denotes the importance these two macronutrients have in regards to post-exercise nutrition and anabolism. Therefore, the purpose of this review is to discuss the impact of dietary protein and carbohydrate intake during the recovery state on muscle protein synthesis and glycogen synthesis.